A psychosocial intervention for individuals with advanced chronic kidney disease: A feasibility randomized controlled trial. Issue 5 (2nd February 2021) - Jenkins, Zoe M.; Tan, Eric J.; O'Flaherty, Emmet; Knowles, Simon; Thompson, David R.; Ski, Chantal F.; Rossell, Susan L.; Coco, Carolee; Ierino, Francesco L.; Gock, Hilton; Castle, David J.
Abstract: Aim: The current study evaluated the feasibility and preliminary efficacy of a psychosocial intervention, the Kidney Optimal Health Program, in reducing symptoms of depression and anxiety in individuals with advanced chronic kidney disease. Methods: Patients with stage 4 or 5 chronic kidney disease were randomized to either a nine‐session psychosocial intervention programme or usual care. Feasibility was assessed through recruitment and retention rates and programme acceptability. Participants completed assessments of depression, anxiety and psychosocial health at baseline and at 3‐, 6‐ and 12‐month follow‐up. A repeated‐measures analysis of variance was used to compare groups on outcomes over time. Results: One hundred and twenty‐eight patients were screened for eligibility; 84 consented to participant and were randomized to receive the intervention ( N = 42) or usual care ( N = 42). 27 (32.1%) participants withdrew prior to baseline assessment. Of those who completed the baseline assessment ( N = 57), trial retention was high (75.4% at 3‐month, 80.7% at 6‐month and 70.2% at 12‐month follow‐up). Participants reported high levels of programme acceptability. The patients who completed the intervention ( N = 17) demonstrated significantly decreased depression at 12‐month follow‐up compared to the usual care group ( N = 13). Conclusion: The results support the feasibility of the Kidney Optimal Health Program intervention in recruitment, retention and programme acceptability with an improved screening protocol. Preliminary support is provided for improvement in depressive symptoms in patients with advanced chronic kidney disease. Further investigation through a fully powered randomized controlled trial is warranted. SUMMARY AT A GLANCE: This study demonstrated that a psychosocial intervention programme, the Kidney Optimal Health Program, is feasible and efficacious in reducing symptoms of depression and anxiety in individuals with advanced chronic kidney disease.